Where are we in our understanding of the association between narcolepsy and one of the 2009 adjuvanted influenza A (H1N1) vaccines?. Issue 4 (July 2016) - Johansen, K.; Brasseur, D.; MacDonald, N.; Nohynek, H.; Vandeputte, J.; Wood, D.; Neels, P.; ,
Abstract: Evaluating new rare serious vaccine safety signals is difficult and complex work. To further assess the observed increase in narcolepsy cases seen in Europe with the 2009 pandemic H1N1 influenza vaccine, the International Alliance for Biological Standardization (IABS) invited a wide range of experts to a one day meeting in Geneva in October 2015 to present data and to discuss the implications. The presentations covered the following topics: clinical picture of childhood narcolepsy following the 2009 H1N1 pandemic vaccination campaigns; epidemiological studies conducted to assess the risk of narcolepsy, other neurological and immune-related diseases following 2009 pandemic H1N1 influenza vaccine; potential biases influencing the different epidemiological study designs; potential genetic contribution to the development of narcolepsy; potential biological mechanisms for development of narcolepsy in this setting including the role of the virus itself, antigenic differences between the vaccines and differences in AS03-adjuvanted vaccines. The presentations were followed by fulsome roundtable discussions. Members from affected families also attended and made informal comments to round out the day's deliberations. This meeting emphasized the value added in bringing together in a neutral setting a wide range of experts and vaccine producers to discuss such a complex new serious adverse event following immunization. Highlights: Available epidemiological and pathophysiological data on the association between narcolepsy and Pandemrix was discussed. Further, possible implications of these findings for seasonal and pandemic influenza vaccines as we move forward was discussed. Finally, options for collaboratively addressing rare vaccine safety event signals given availability of newer tools and knowledge was discussed.